Life-like behavior emerging in active and flexible microstructures - Mengshi Wei; Daniela J. Kraft (Proceedings of the National Academy of Sciences, 2026)
Many organisms leverage an interplay between shape and activity to generate motion and adapt to their environment. Embedding such mechanical feedback into synthetic micrometer-sized robots could eliminate the need for sensors, software, and actuators. Current active micrometer-scale systems, however, do not possess a flexible body with which they can autonomously sense and react to their environment. Here, we experimentally realize active and flexible structures by concatenating anisotropic micrometer-sized units using 3D microprinting and activating them using AC fields. We demonstrate that this minimal design integrates mechanical feedback between activity and shape, resulting in a rich array of modes of motion—including railway and undulatory locomotion, rotation, and beating. It furthermore gives rise to emergent sense-response abilities, which enable autonomous reorientation, navigation, and collision avoidance. Our approach offers a versatile platform for designing biomimetic model systems and autonomously operating microrobots with embodied intelligence.